PENERAPAN MODEL PEMBELAJARAN INKUIRI UNTUK MENINGKATKAN HASIL BELAJAR IPA SISWA KELAS IV SDS AISYIYAH BENGKALIS - Aina Aina; Syahrilfuddin Syahrilfuddin; Lazim. N Lazim. N (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: The research problem is the poor performance of fourth grade students learn science SDS Aisyiyah Bengkalis. Complete Minimal Value Criteria (KKM) IPA set school is 65.00. among 23 students only 10 students who achieve KKM.. This research is a classroom action research (CAR) conducted aims to improve learning outcomes fourth grade science students SDS Aisyiyah Bengkalis by applying inquiry learning model. Data collection instrument using teacher and student activity sheet and learning outcomes. Activities of teachers at the first meeting I cycle a percentage of 60.00% gain enough categories, at the second meeting with a percentage increase of 75,00% both categories. Furthermore, the first meeting of the second cycle of teacher activity also increased the percentage to 85.00% good category and at the second meeting of the second cycle increased again with a percentage of 95.00% excellent category. Activities of students at the first meeting of the first cycle obtain sufficient percentage of 55.00% category, at the second meeting of the first cycle increased percentage of 65.00% into both categories, at the first meeting of the second cycle increased with the percentage of 75.00% both categories. At the second meeting of the second cycle increased with the percentage of 90.00% excellent category. From the average results of study before action 62.17 increased to 64.56 in Cycle I. In the second cycle increased 71.65. The results of this study prove that the implementation of inquiry learning model can improve learning outcomes fourth grade science students SDS Aisyiyah Bengkalis.Keywords: Inquiry Learning Model, Science Learning Outcomes